2015
DOI: 10.1111/wrr.12326
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Greek family members living with leg ulcer patients

Abstract: Leg ulcers have been shown to have a significant impact on a patient's quality of life (QoL). Little is known, however, about the secondary impact of the disease on the QoL of the relatives and partners of patients with leg ulcers. The aim of this study was to explore the impact of chronic leg ulcers on the lives of both patients and their family members. Two hundred sixteen patients with leg ulcers and their family members were recruited. All patients entered were evaluated for QoL using the Dermatology Life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
(31 reference statements)
0
15
1
2
Order By: Relevance
“…In another study, where the health-related QoL, self-esteem, and functional status had been investigated in leg ulcer patients and a control group, significant differences for physical functioning, emotional role, bodily pain, general health, and vitality could be found. 44 Kouris et al 45 confirmed a significant impairment in QoL, self-esteem, anxiety, and social isolation in a case-control study of leg ulcer patients. …”
Section: Depression and Painmentioning
confidence: 96%
“…In another study, where the health-related QoL, self-esteem, and functional status had been investigated in leg ulcer patients and a control group, significant differences for physical functioning, emotional role, bodily pain, general health, and vitality could be found. 44 Kouris et al 45 confirmed a significant impairment in QoL, self-esteem, anxiety, and social isolation in a case-control study of leg ulcer patients. …”
Section: Depression and Painmentioning
confidence: 96%
“…In addition, FDLQI scores were found to be higher in caregivers of patients whose age was between 10 and 20 . Family members living with leg ulcer patients also showed highly affected QoL and their mean FDLQI score was reported to be 14.4 and clearly related to the patients' QoL . In this study, no cases of vitiligo, leg ulcers or epidermolysis bullosa were included.…”
Section: Discussionmentioning
confidence: 85%
“…The FDLQI has been translated into many languages . In addition to validation studies on groups of various skin diseases, the impact of specific skin diseases on patients' family members' QoL has been investigated . The QoL of family members of vitiligo patients showed a mean FDLQI score of 10.3 and their lives were shown to be affected in various aspects .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Italian, Persian and Ukrainian versions have been published. Other articles have described the use of the FDLQI …”
Section: Resultsmentioning
confidence: 99%